A single dose of the Biontech/Pfizer BNT162b2 vaccine protected elderly residents from severe COVID‐19 during a SARS‐coronavirus‐2 outbreak in a senior citizen home in Germany. Issue 4 (16th September 2021) - Schwarzer, Rolf; Freys, Sabine D.; Neuwinger, Nick; Beikert, Nina; Eberspächer, Bettina; Edelmann, Anke; Zuchowski, Marta; Slothouwer, Inga; Stein, Angela; Theil, Kathrin; Menzel, Peter; Hofmann, Jörg
Abstract: Background : A total of 62/66 (93.9%) residents in a senior citizen home in Bremen, Germany, received the first dose of the Biontech/Pfizer vaccine BNT162b2 on December 27th 2020. After routine severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antigen tests showed positive results on January 5th, all residents and staff were tested by RT‐PCR. Results : Nine staff members and 23 residents had a positive result. PCR positive staff members reported mild to severe COVID‐19 symptoms, one was hospitalized. None of them had been vaccinated. In contrast, the vaccinated residents reported no or only mild symptoms. Sequencing of the SARS‐CoV‐2 genomes of infected individuals revealed a monophyletic origin of the outbreak within the PANGO lineage B.1.177.86. Conclusions : In summary, our data show that partial vaccination prevented severe COVID‐19 among the residents during this local SARS‐CoV‐2 outbreak, suggesting a high effectiveness of even a single vaccine dose, but also emphasize that asymptomatic individuals might still be carriers/spreaders. Abstract : Background : A total of 62/66 residents in a senior citizen home in Bremen, Germany, received the first dose of the Biontech/Pfizer vaccine BNT162b2 on December 27th 2020. After routine SARS‐CoV‐2 antigen tests showed positive results on January 5th, all residents and staff were tested by RT‐PCR. Results : Nine staff members and 23 residents had a positive result. PCR positive staff members reported mild to severe COVID‐19 symptoms, one was hospitalized. None of them had been vaccinated. In contrast, the vaccinated residents reported no or only mild symptoms. Sequencing of the SARS‐CoV‐2 genomes of infected individuals revealed a monophyletic origin of the outbreak within the PANGO lineage B.1.177.86. Conclusions : In summary, our data show that partial vaccination prevented severe COVID‐19 among the residents during this local SARS‐CoV‐2 outbreak, suggesting a high effectiveness of even a single vaccine dose, but also emphasize that asymptomatic individuals might still be carriers/spreaders.